2005
DOI: 10.1093/rheumatology/keh599
|View full text |Cite
|
Sign up to set email alerts
|

Is musculoskeletal pain more common now than 40 years ago?: two population-based cross-sectional studies

Abstract: Objective. To test the hypothesis that the prevalence of specific musculoskeletal pain symptoms has increased over time in the northwest region of England. To meet this objective we have examined the difference in the prevalence of low back, shoulder and widespread pain between the 1950s and today using historical data collected by the Arthritis Research Campaign (arc). Methods. Two cross-sectional surveys conducted over 40 yr apart in the northwest region of England. The status of two regional pain sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 35 publications
8
110
2
3
Order By: Relevance
“…It could be that the actual prevalence has not changed but the reporting has; or it could be that the questions used to assess the prevalence have changed; or LBP prevalence really increased due to life style changes of the population. Harkness et al showed there were significant differences in the prevalence of pain increasing from 2-to 4-fold between two surveys (47). Chronic pain is a common symptom and significant problem for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that the actual prevalence has not changed but the reporting has; or it could be that the questions used to assess the prevalence have changed; or LBP prevalence really increased due to life style changes of the population. Harkness et al showed there were significant differences in the prevalence of pain increasing from 2-to 4-fold between two surveys (47). Chronic pain is a common symptom and significant problem for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Harkness et al, in a 2000 publication, showed that there was a large difference in the prevalence of musculoskeletal pain over a 40-year period under investigation [9]. The results showed that overall, the prevalence of low back pain increased from 8.1 to 17.8% in males, and it increased from 9.1 to 18.2% in females.…”
mentioning
confidence: 98%
“…Chronic persistent pain can cause significant impairment of physical and psychological health, and performance of social responsibilities, including work and family life [1][2][3][4][5][6][7][8][9][10][11][12]. While modern medicine has shown significant improvements in the understanding of pain (including diagnosis and treatment), chronic pain continues to be an epidemic resulting in vocational, social and family discord, which may make the difference between life and death, and is accompanied by claims of inadequate treatment [1][2][3][4][5][13][14][15][16][17].…”
mentioning
confidence: 99%
“…12 Therefore depression typically presents somatically and pain appears to be a core feature of depression. In Ireland as elsewhere in the western world, pain medicine services have evolved in most healthcare settings to meet the needs of patients with chronic pain who are increasing in prevalence 13 and who typically have marked disability. Unfortunately these services have not always been resourced or developed to include access to assessment by a mental health professional.…”
Section: Depression and Somatic Symptomsmentioning
confidence: 99%